O elegante controle do trabalho em “O Diabo veste Prada” - Oliveira, Ana Virgínia Andrade de (2017)
The work has a real and significant role in the people’s life, though its features have changed over time, due to scientific, technological, market and socio-historical advances, which impose new challenges and new demands on the contemporary worker. This article aimed to illustrate the characteristics of the Toyotism, specially on the matter of managing subjective labor relations and its efects on the workers. For that, it was made a film analysis of the cinematographic work “The Devil wears Prada”, consisting of: definition of the object and theme of research; film selection, external and internal rewiews; comparison and analysis of the contentes. After the scenes analysis, it was found that the most striking feature of this model is the flexibility and also that the movie illustrates what is presented in the scientific literature about this theme, what validates the experience of insecurity, individualism and competitiveness, which are widespreads in the Toyota model. It is expected to clarify the aspects of this work model, so that helps the positioning of psychologists in their practice in labour contexts.